2020
DOI: 10.1124/jpet.120.000110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Application of CHF6467, a Mutated Form of Human Nerve Growth Factor, on Skin Wound Healing in Diabetic Mice

Abstract: Nerve growth factor (NGF) is the protein responsible for the development and maintenance of sensory skin innervation. Given the role of appropriate innervation in skin healing, NGF has been indicated as a possible prohealing treatment in pathological conditions characterized by nerve ending loss, such as chronic ulcers in diabetes, however its use as a therapeutic agent is limited by its hyperalgesic effect. We tested the effect of topical application of the non-algogenic NGF derivative hNGFP61S/R100E in two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…This molecule is a rhNGF containing an amino acid substitution, which removed the NGF-related hyperalgesic effect, while maintaining its ability to induce wound healing. CHF6467 treatments of pressure ulcers in diabetic mice accelerated skin repair, increasing re-epithelization, re-innervation, and revascularization (Giuliani et al, 2020). Our results confirmed other studies (Muangman et al, 2004), with the remarkable difference that we used a non-algogenic rhNGF, thus potentially overcoming the main limitation to the clinical application of NGF (Giuliani et al, 2020).…”
Section: Skinsupporting
confidence: 85%
See 1 more Smart Citation
“…This molecule is a rhNGF containing an amino acid substitution, which removed the NGF-related hyperalgesic effect, while maintaining its ability to induce wound healing. CHF6467 treatments of pressure ulcers in diabetic mice accelerated skin repair, increasing re-epithelization, re-innervation, and revascularization (Giuliani et al, 2020). Our results confirmed other studies (Muangman et al, 2004), with the remarkable difference that we used a non-algogenic rhNGF, thus potentially overcoming the main limitation to the clinical application of NGF (Giuliani et al, 2020).…”
Section: Skinsupporting
confidence: 85%
“…Besides its role in angiogenesis (Calzà et al, 2001;Ahluwalia et al, 2017; and its action on skin cells (Gostynska et al, 2020), NGF may act by improving local reinnervation, fundamental to the wound healing process (Kiya and Kubo, 2019). Our transcriptomic study on the CHF6467 molecule also points to the modulation of Akt/mTOR signaling as the main driver of NGF action (Giuliani et al, 2020). This pathway is in fact in involved in the wound healing process (Huang et al, 2015;Jere et al, 2019) and is regarded as a therapeutic target (Squarize et al, 2010).…”
Section: Skinmentioning
confidence: 62%
“…PLLA loaded with 15% GM18 (PLLA15GM18) was chosen, based on the results of the GM18 release tests and from previous in vitro studies on mesenchymal stem cells . This experiment was conducted in the pressure ulcer model in diabetic mice, as already established and characterized in our lab. , Photos of representative ulcers from the three experimental groups at 14 days from the first medication are shown in Figure A. The repaired area was measured as % value on day 14 compared to day 3 (when surgical curettage and the first medication were performed) and expressed as “residual wound area”.…”
Section: Resultsmentioning
confidence: 99%
“…Db/db mice are homozygous for the diabetes spontaneous mutation ( Lepr db ) on a C57BL/6 J genetic background, and develop progressive insulin resistance, hyperglycemia, and obesity from 4 to 8 weeks of age. This is followed by progressive sensory loss, electrophysiological impairments, and skin innervation loss (De Gregorio et al 2018 ; Giuliani et al 2020 ), which stabilize from 16 weeks of age onwards (Shi et al 2013 ; Tang et al 2019 ), mimicking the main pathophysiological aspects observed in human diabetic neuropathy (Yorek 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…AKT-pathway dysfunction in diabetic mice, which has been indicated as a possible cause of wound healing impairment (Huang et al 2015 ), is somewhat complex, involving AKT isoform switches, phosphorylation, and de-phosphorylation in the different phases of wound healing (coagulation, inflammation, proliferation, and remodeling) (Maurer et al 2014 ; Vines et al 2019 ; Jere et al 2019 ; Khorami et al 2020 ). A transient pharmacological activation of the PI3K-Akt-mTOR signaling axis has been considered a novel clinical intervention strategy to accelerate wound (ulcer) healing (Squarize et al 2010 ), and we recently demonstrated that the pro-healing effect of a mutated form of rhNGF includes Akt regulation (Giuliani et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%